A different way of foreign trade with the soviet union in the early turkish republican period: Unlicensed import trade [Erken cumhuriyet döneminde sovyetler birliği ile diş ticaretin başka bir yolu: Lisanssiz ıthalat] - (:unkn) unknown (Hacettepe University, 2019)
Unlicensed import trade was the most important right that was given by the Soviet Union to Turkey in order to provide a stable foreign trade between the two countries from 1924 to 1927. The Soviet Union began to nationalize all firms in their domestic economy and imposed a state monopoly on foreign trade after the revolution. In the mean time Turkey did not accept any intervention in its economy, and it was not easy to force the Turkish government to allow Soviet state monopoly foreign trade institutions into Turkey. Hence, the Soviet Union could not establish its trade institutions according to its foreign trade rules. This caused a problematic trade relationship between the two countries until1927, when a trade agreement was finally signed. Because of the sanctions and trade bans that were implied by Western countries to the Soviet Union, Soviet bureaucrats tried to put higher priority on their trade relationships with Iran and Turkey in the 1920s. Thus, the Soviet Union looked for every opportunity that it could help to sign trade agreements with Turkey and Iran. A trade agreement could establish Soviet trade institutions with all the desired recognitions and bring about an advantage in defending Soviet foreign trade interests in Turkey and Iran. The Ministry of Trade gave permission to import merchandise without any license from Turkey and Iran to the Soviet Union as long as the origin of them was proved to belong to the two countries. At first Turkish merchants benefited from unlicensed imports to the Soviet Union. Then, Soviet trade institutions, Arcos, Russoturk and the Transcaucasian Trade Organization, also benefited from unlicensed import to the Soviet Union. In a very short time unlicensed import rates caught and passed licensed imports. Consumer goods were most common in unlicensed import trade at the beginning. Later on the Soviet Union imported mostly raw materials by unlicensed import trade from Turkey. Therefore, the unlicensed trade system was thought to persuade Turkey to sign a trade agreement by Soviet bureaucrats. Unlicensed import trade from Turkey provided the material to increase industrial production in the Soviet Union, and contributed to foreign trade between the two countries. © 2019, Hacettepe University. All rights reserved.
Keywords: Arcos; Russoturk; Soviet fairs; Soviet union; Transcaucasia trade organization; Turkey; Unlicensed import trade